Piezo1: the key regulators in central nervous system diseases - Xu, Yi; Wang, Yuheng; Yang, Yanling; Fang, Xiaowei; Wu, Lidong; Hu, Jialing; Li, Jin; Mei, Shuchong (Frontiers in Cellular Neuroscience, 2024)
The occurrence and development of central nervous system (CNS) diseases is a multi-factor and multi-gene pathological process, and their diagnosis and treatment have always posed a serious challenge in the medical field.Therefore, exploring the relevant factors in the pathogenesis of CNS and improving the diagnosis and treatment rates has become an urgent problem.Piezo1 is a recently discovered mechanosensitive ion channel that opens in response to mechanical stimuli. A number of previous studies have shown that the Piezo channel family plays a crucial role in CNS physiology and pathology, especially in diseases related to CNS development and mechanical stimulation. This article comprehensively describes the biological properties of Piezo1, focuses on the potential association between Piezo1 and CNS disorders, and explores the pharmacological roles of Piezo1 agonists and inhibitors in treating CNS disorders.